PENGARUH KONTEN INSTAGRAM TERHADAP KEPUTUSAN KONSUMEN MEMILIH POTONG RAMBUT DI BE_HAIRCUT BARBERSHOP - Nurwulan, Adinda Suci; Kusmayadi, Dicki (Unitri Press, 2024)
Purpose: This research was conducted with the aim of finding out how the influence of content on the Instagram application has on every consumer's decision to choose a haircut at be_haircut barbershop. Methods: This research uses a quantitative approach with data collection methods through questionnaires. The research sample was 100 respondents who were followers of Instagram @be_haircut. Analysis data: this research uses analysis of respondents' level of achievement, simple regression, coefficient of determination and hypothesis testing (t-test). Results and discussion: through analysis results using respondents' achievement levels, the Instagram content variable that really influences consumer decisions is the feed indicator. Meanwhile, of the consumer decision variables that have the greatest influence on consumers' decisions to choose a haircut at be_haircut barbershop are product choice indicators. Conclusion: after collecting and processing data in the form of statistical tests using SPSS version 25, the conclusion was obtained, namely that there is a significant influence between Instagram content on consumers' decisions to choose a haircut at be_haircut barbershop.